Spironolactone differently influences remodeling of the left ventricle and aorta in L-NAME-induced hypertension - Simko, F; Matúsková, J; Lupták, I; Pincíková, T; Krajcírovicová, K; Stvrtina, S; Pomsár, J; Pelouch, V; Paulis, L; Pechánová, O (Physiological research, 2007)
Aldosterone receptor antagonist, spironolactone, has been shown to prevent remodeling of the heart in several models of left ventricular hypertrophy. The aim of the present study was to determine whether the treatment with spironolactone can prevent hypertension, reduction of tissue nitric oxide synthase activity and left ventricular (LV) and aortic remodeling in N(G)-nitro-L-arginine methyl ester (L-NAME)-induced hypertension. Four groups of rats were investigated: control, spironolactone (200 mg/kg), L-NAME (40 mg/kg) and L-NAME + spironolactone (in corresponding dosage). Animals were studied after 5 weeks of treatment. The decrease of NO-synthase activity in the LV and kidney was associated with the development of hypertension and LV hypertrophy, with increased DNA concentration in the LV, and remodeling of the aorta in the L-NAME group. Spironolactone prevented the inhibition of NO-synthase activity in the LV and kidney and partially attenuated hypertension and LVH development and the increase in DNA concentration. However, remodeling of the aorta was not prevented by spironolactone treatment. We conclude that the aldosterone receptor antagonist spironolactone improved nitric oxide production and partially prevented hypertension and LVH development without preventing hypertrophy of the aorta in NO-deficient hypertension. The reactive growth of the heart and aorta seems to be controlled by different mechanisms in L-NAME-induced hypertension.
Keywords: antagonisté mineralokortikoidních receptorů; aorta; NG-Nitroarginine Methyl Ester; Ventricular Remodeling; Hypertension; ledviny; spironolakton; oxid dusnatý; Kidney; synthasa oxidu dusnatého; krysa rodu Rattus; Antihypertensive Agents; hypertrofie levé komory srdeční; Hypertrophy, Left Ventricular; zvířata; proliferace buněk; Nitric Oxide; potkani Wistar; časové faktory; DNA Replication; Mineralocorticoid Receptor Antagonists; Rats, Wistar; krevní tlak; Male; hypertenze; replikace DNA; Cell Proliferation; Heart Ventricles; Spironolactone; Rats; NG-nitroargininmethylester; Animals; antihypertenziva; mužské pohlaví; Aorta; Blood Pressure; remodelace komor; Time Factors; srdeční komory; Nitric Oxide Synthase